Respuesta :

Answer:

[tex]y=-\frac{1}{3}x+4[/tex]

Step-by-step explanation:

step 1

Find the slope of the perpendicular line

we know that

If two lines are perpendicular, then their slopes are opposite reciprocal

(the product of their slopes is equal to -1)

In this problem

we have

[tex]y=3x+1[/tex]

The equation of the given line is [tex]m=3[/tex]

so

the slope of the perpendicular line to the given line is

[tex]m=-\frac{1}{3}[/tex]

step 2

Find the equation of the line in point slope form

[tex]y-y1=m(x-x1)[/tex]

we have

[tex]m=-\frac{1}{3}[/tex]

[tex](x1,y1)=(6,2)[/tex]

substitute

[tex]y-2=-\frac{1}{3}(x-6)[/tex]

Convert to slope intercept form

[tex]y=mx+b[/tex]

Distribute right side

[tex]y-2=-\frac{1}{3}x+2[/tex]

[tex]y=-\frac{1}{3}x+2+2[/tex]

[tex]y=-\frac{1}{3}x+4[/tex]